Cognitive Aspects of a Poetic Work - Yerzhanova, Sovetkhan B. Tleubayev, Alua B. Temirbolat, Mukhit M. Kozhashev, GulmariyaT. Ospanova, Saule B. (Opción, 1970)
The article substantiates the idea that the cognitive approach is productive for studying the creativity of poets. Its use allows, firstly, to enrich the methodological apparatus of modern literary study; secondly, to reveal more deeply the psychology of the author, the characters, the reader, their ideas about the surrounding reality; thirdly, to understand the mechanisms of the writer’s thinking and their reflection on various levels of poetics of works. As an object of analysis, the work of the classics of world literature I. Annenskii, Zh. Zhabaev, V. Nabokov, M. Rofu, belonging to different national cultures, directions and styles, was chosen.